Concurrent chronic lymphocytic leukemia and COVID-19: A comprehensive review of epidemiological, diagnostic, and therapeutic challenges. (2021) - Roosta, Yousef; Behzadi, Farhad; Askari, Elham; Raeisi, Mortaza; Danandeh Mehr, Amin; Nouri-Vaskeh, Masoud
Highlights: Diagnostic interaction between CLL and COVID-19 due to different behavior of lymphocyte count remains as a major challenge. CLL patients have a lower rate of anti-SARS-CoV-2 IgG development emphasizing notably difference in patients' immune response to COVID-19 or potential vaccination in CLL patients. Summing the evidences show unacceptable therapeutic outcome in patients with concurrent CLL and COVID-19 needing revise currently and running protocols. The treatment protocol recommended by experts has been very diverse and therefore there is not a standard protocol acceptable to everyone. Abstract: A comprehensive review of the literature on chronic lymphocytic leukemia (CLL) patients and recommendations regarding the evaluation and treatment of these patients was conducted. The overall prevalence of CLL and COVID-19 concurrence was found to be 0.6% (95%CI: 0.5% to 0.7%). Diagnostic interaction between CLL and COVID-19 remains a major challenge. Also, CLL patients have a lower rate of anti-SARS-CoV-2 IgG development. Evidences show the unacceptable therapeutic outcome in these patients. Although the CLL-COVID-19 occurrence is associated with adverse clinical consequences, no general and standard agreement has yet been presented for the management and treatment of this disease.